Bioactivity and chemical composition of Humulus Lupulus L. for cosmetic use - Spafiu, Paula Raluca (2020)
Humulus lupulus L. is use as a flavoring and stabilizing agent for beer, giving aromas and flavors. Can also be use in cosmetics,for its antibacterial/antioxidant effect Prepare a cosmetic gel formulations with phenolic extracts of the flowers and vegetative parts and analyze their stability, antioxidant/antimicrobial activity. Phenolic compounds were extracted with ethanol/water. Humulus lupulus varieties used were (vegetative parts):Chinook, Cascade, Polaris, Centennial, Nugget, and (flowers):Cascade, Polaris, Nugget and Centennial. Gel formulations were prepared, using Carbopol and Methyl-Cellulose, with 3 concentrations: 2.5, 5 and 7.5%. For stability we test:pH, density, temperature, light, centrifuge, vibration and UV spectrophotometric analysis. Organoleptic characteristics:odor, color and aspect was test. Extracts were evaluated for antimicrobial activity by agar diffusion assays of E.coli and Candida albicans. Results:pH have no alteration. Centrifuge and vibration tests, most of the gel formulations did not present phase separation. Density was 1.2-1.3 g/cm3. Candida Albicans test, have no result but bacteria test shown that E.coli was sensible for all concentrations. Flower hydroalcoolic extract are richest in phenolic compounds than the vegetative parts. Phenols composition is different in all varieties. Conclusion:Gels are stable and can be used as a cosmetic in further studies. Humulus lupulus showed positive antibacterial result.